Systematic Literature Review (SLR): Transparency And Accountability In Village Financial Management - Desak Nyoman Lia Lestari; I Gusti Made Darma (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
Village financial management plays a crucial role in supporting sustainable development and enhancing community welfare. With the enactment of Law No. 6 of 2014, villages in Indonesia have been granted autonomy to manage their finances, including the allocation and utilization of Village Funds. However, the primary challenges remain the lack of transparency and accountability, which often result in budget mismanagement and diminished public trust. This study adopts a systematic literature review (SLR) methodology, analyzing seven relevant studies on transparency, accountability, and village financial management. The findings reveal that transparency in disclosing information regarding the allocation and expenditure of village funds fosters greater community participation and enhances public trust. Furthermore, accountability—defined as adherence to legal regulations and compliance with government accounting standards—emerges as a critical factor in maintaining legitimacy and sustaining public confidence. The integration of technology, such as the Village Financial Information System (Sistem Keuangan Desa or Siskeudes), significantly bolsters both transparency and accountability by streamlining financial processes and enabling real-time monitoring. Additionally, effective village financial management necessitates a synergistic approach, combining the technical precision of accounting practices with the participatory and inclusive nature of public administration. Community involvement is identified as a cornerstone of this system, ensuring a responsive and sustainable framework for financial oversight and governance. This research underscores the importance of aligning technical and social dimensions in village financial management to achieve governance that is both effective and sustainable